White collar. The complete first season [videorecording (DVD)] - Eastin, Jeff; Bomer, Matthew, 1977-; DeKay, Tim, 1963-; Thiessen, Tiffani, 1974-; Garson, Willie, 1964-2021- (20th Century Fox Home Entertainment, 2010)
Charming con man Neal Caffrey escapes from a maximum security prison, only to be recaptured by his nemesis, FBI Agent Peter Burke. With few options, Caffrey agrees to help the bureau bring down other elusive criminals in exchange for his eventual freedom. But before long, Caffrey finds himself playing a game of cat and mouse with those who want him back in prison or dead.